2022
DOI: 10.1038/s42003-022-03914-8
|View full text |Cite
|
Sign up to set email alerts
|

Paternal low protein diet perturbs inter-generational metabolic homeostasis in a tissue-specific manner in mice

Abstract: The underlying mechanisms driving paternally-programmed metabolic disease in offspring remain poorly defined. We fed male C57BL/6 mice either a control normal protein diet (NPD; 18% protein) or an isocaloric low protein diet (LPD; 9% protein) for a minimum of 8 weeks. Using artificial insemination, in combination with vasectomised male mating, we generated offspring using either NPD or LPD sperm but in the presence of NPD or LPD seminal plasma. Offspring from either LPD sperm or seminal fluid display elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 66 publications
2
14
1
Order By: Relevance
“…Further, the increased plasma leptin in the HF and HFCR-I offspring shows that they are prone to leptin resistance irrespective of their FER differences, indicating that they exhibit different pathophysiology of obesity. In mice, the father's high-fat diet led to increased fat mass in the offspring [55], and the paternal low-protein diet in rats was also associated with increased fat mass and organ weights in the offspring [24,57]. The present ndings are also in line with those of previous studies in which the total body fat percentage increased with increased adiposity index in HF and HFCR-I offspring, demonstrating that they exhibit imbalanced body fat accumulation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, the increased plasma leptin in the HF and HFCR-I offspring shows that they are prone to leptin resistance irrespective of their FER differences, indicating that they exhibit different pathophysiology of obesity. In mice, the father's high-fat diet led to increased fat mass in the offspring [55], and the paternal low-protein diet in rats was also associated with increased fat mass and organ weights in the offspring [24,57]. The present ndings are also in line with those of previous studies in which the total body fat percentage increased with increased adiposity index in HF and HFCR-I offspring, demonstrating that they exhibit imbalanced body fat accumulation.…”
Section: Discussionsupporting
confidence: 91%
“…High-fat diet exposure in fathers leads to increased serum lipid and lipid synthesis in offspring [19,58,59]. In mice, a paternal low-protein diet has also shown increased total cholesterol and triglycerides in the offspring [57] and increased lipogenesis gene expression in male offspring [60]. The present study revealed greater plasma lipid levels in HF and HFCR-I offspring than in HFCR-II offspring, suggesting that a paternal high-fat diet and CR lead to obesogenic effects in offspring, which was further con rmed by their increased mRNA expression of the lipid synthesis genes FAS and SCD1 and decreased expression of the lipid β-oxidation genes CPT1 and ACOX2.…”
Section: Discussionmentioning
confidence: 99%
“…In conditions like obesity and metabolic syndrome, high TG levels are often accompanied by increased inflammation in adipose tissue. Accumulation and activation of inflammatory cells in adipose tissue release pro-inflammatory factors such as prostaglandins and leukotrienes [44]. These inflammatory lipid mediators not only intensify systemic inflammation but may also lead to more severe pain and other related symptoms in EMS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In another study using artificial ejaculation in the European whitefish Coregonus lavaretus , the presence of foreign seminal fluid in the ejaculate has been shown to the increase swimming performance in the offspring [ 57 ]. The links between paternal nutrition and metabolic dysfunction in the offspring have also been repeatedly shown in mice to be mediated by either sperm-related or seminal fluid-mediated processes [ 58 , 59 , 60 ].…”
Section: Relationships Between the Seminal Fluid Content And The Phen...mentioning
confidence: 99%